Electronic Cigarette using in Surabaya’s Personal Vaporizer Community - Apsari Damayanti (Jurnal Berkala Epidemiologi, 2016)
At present, the number of electronic cigarette users has increased. Electronic cigarette users in 2010-2011 in Indonesia reached 0.5%. This study aims to describe the use of electronic cigarettes in the Surabaya Personal Vaporizer Community. This type of research is a descriptive observational study with a cross-sectional design. This research was conducted on 31 members of the Surabaya Personal Vaporizer Community. The dependent variable in this study is the use of electronic cigarettes, while the independent variables are knowledge, affordability, and family factors. The results showed that most electronic cigarette users aged 26 - 35 years (54.8%), were male (96.8%), had a high school education up to college (100%), worked as an employee (71%), had a history of smoking (93.6%), and reasoned as an effort to stop smoking (80.6%). The analysis by calculating the prevalence ratio shows that good knowledge about electronic cigarettes (PR = 0.89) and no family support (PR = 0.95) is a protective factor for not using electronic cigarettes, while the affordability of costs for electronic cigarette liquids is risk factors for using electronic cigarettes (PR = 1.32). Of all the variables studied, only the affordability of costs for electronic cigarette liquids is a risk factor for heavy electronic cigarette use. Therefore, education about the dangers of electronic cigarettes as well as the intended use of electronic cigarettes must continue and supervision of electronic cigarette use needs to be done.